'People have a knack for making you feel excluded if they catch on to your difference': Transgender experiences of exclusion in sport. - Mitchell, David; Hargie, Owen D.W.; Somerville, Ian J.A. (My University, 2017)
While there is a growing literature in the field of gender, sexuality and sport, there is a dearth of research into the lived experiences of transgender people in sport. The present study addresses this research gap by exploring and analysing the accounts of transgender people in relation to their experiences of sport and physical activity. These are examined within the theoretical rubrics of social exclusion and minority stress theory. The findings from in-depth interviews with 10 transgender persons are detailed. Four interconnected themes emerged from the interviewee accounts: the intimidating nature of the changing/locker room environment; the impact of alienating sports experiences at school; the fear of public space and how this drastically constrained their ability to engage in sport and physical activity; and the overall effects of being denied the social, health and wellbeing aspects of sport. The findings are discussed in relation to the distinctive quality of transgender exclusion, and the related distal and proximal stressors experienced by this particular minority group.
PUBLISHED
Keywords: LGBT; Minority stress theory; Social exclusion; Sport; Transgender people; Inclusive Society; Sociology; Sport Studies